Smoking cessation assistance among pneumologists and thoracic surgeons in Switzerland: a national survey - Minervini, Fabrizio; Kestenholz, Peter; Rassouli, Frank; Pohle, Susanne; Mayer, Nora (Frontiers in Health Services, 2024)
ObjectiveSmoking, with a prevalence of about 25%–30% in Switzerland, is proven to cause major systemic, avoidable diseases including lung cancer, increasing societies morbidity and mortality. Diverse strong quitting smoking recommendations have been made available providing advice facilitating smoking cessation globally. In other European countries like Germany, clinical practice guidelines for smoking cessation services have been implemented. However, in Switzerland, there is still no national consensus on a comprehensive smoking cessation program for lung cancer patients nor on the adequate provider. Our primary aim was to assess the current status of smoking cessation practice among specialists, mainly involved in lung cancer care, in Switzerland in order to uncover potential shortcomings.Material and methodsA self-designed 14-items questionnaire, which was reviewed and approved by our working group consisting of pneumologists and thoracic surgeons, on demographics of the participants, the status of smoking cessation in Switzerland and specialists' opinion on smoking cessation was sent to thoracic surgeons and pneumologists between January 2024 and March 2024 via the commercially available platform www.surveymonkey.com. Data was collected and analysed with descriptive statistics.ResultsSurvey response rate was 22.25%. Smoking cessation was felt to positively affect long term survival and perioperative outcome in lung cancer surgery. While 33 (37.08%) physicians were offering smoking cessation themselves usually and always (35.96%), only 12 (13.48%) were always referring their patients for smoking cessation. Patient willingness was clearly identified as main factor for failure of cessation programs by 63 respondents (70.79%). Pneumologists were deemed to be the most adequate specialist to offer smoking cessation (49.44%) in a combination of specialist counselling combined with pharmaceutic support (80.90%).ConclusionThe development of Swiss national guidelines for smoking cessation and the implementation of cessation counselling in standardized lung cancer care pathways is warranted in Switzerland to improve long-term survival and perioperative outcome of lung cancer patients.